The unrealized potential of presidential coalitions in Colombia (2016)
This chapter analyzes the current Colombian legislative process in terms of the input and output of the legislative agenda during four presidential periods (1998–2014). During this time, the electoral and party system changed significantly, while presidential constitutional power and the internal rules of Congress remained unchanged. Importantly, changes in Colombia’s party system have coincided with the formation of multi-party coalition cabinets. However, this chapter shows that the growth in such coalitions does not lead to any additional advantages for these presidents. It argues two main factors explain this outcome: first, legislators face incentives to focus on developing personal constituencies rather than supporting their party’s collective agenda; second, decentralized formal institutional rules in Congress empower deputies to influence both the agenda and the content of bills, which affects the legislative efficiency of the governing coalition. As a result, executive failures remain just as frequent despite large and increasingly formalized coalitions.